Seismic assessment of a 5-storey retrofitted rc building - Bark, Hussein Ali; Markou, George; Mourlas, Christos; Papadrakakis, Manolis (My University, 2016)
Due to severe damages on structures caused by earthquakes different approaches were introduced to enhance their carrying capacity. The most common one is retrofitting, which is a technique used to improve the structural capacity of a building that is found to be inadequate against earthquake loads. The problems that arise when retrofitting reinforced concrete structures, is the use of objective and sound methods that will provide the engineer with the tools to assess the final design. This work aims to alleviate this restriction by performing a complete study of a 5-storey reinforced concrete structure that was retrofitted with reinforced concrete shear walls through the use of 3D solid finite elements. Cracking is treated with the smeared crack approach and the steel reinforcement is simulated by embedded rod elements. This detailed modeling approach is applied for the first time so as to perform a full pushover analysis of a 5-storey RC retrofitted building. The numerical results illustrate that the proposed assessment approach is computationally accurate. Furthermore, the use of parallel processing is required so as to decrease the computational demand when dealing with full scale models.
Keywords: Retrofitted Structure; Reinforced Concrete Modeling; Finite Element Method; Seismic Assessment